WSe2 Homojunction Devices: Electrostatically Configurable as Diodes, MOSFETs, and Tunnel FETs for Reconfigurable Computing. Issue 41 (25th August 2019) - Pang, Chin‐Sheng; Chen, Chin‐Yi; Ameen, Tarek; Zhang, Shengjiao; Ilatikhameneh, Hesameddin; Rahman, Rajib; Klimeck, Gerhard; Chen, Zhihong
Abstract: In this paper, electrostatically configurable 2D tungsten diselenide (WSe2 ) electronic devices are demonstrated. Utilizing a novel triple‐gate design, a WSe2 device is able to operate as a tunneling field‐effect transistor (TFET), a metal–oxide–semiconductor field‐effect transistor (MOSFET) as well as a diode, by electrostatically tuning the channel doping to the desired profile. The implementation of scaled gate dielectric and gate electrode spacing enables higher band‐to‐band tunneling transmission with the best observed subthreshold swing (SS) among all reported homojunction TFETs on 2D materials. Self‐consistent full‐band atomistic quantum transport simulations quantitatively agree with electrical measurements of both the MOSFET and TFET and suggest that scaling gate oxide below 3 nm is necessary to achieve sub‐60 mV dec −1 SS, while further improvement can be obtained by optimizing the spacers. Diode operation is also demonstrated with the best ideality factor of 1.5, owing to the enhanced electrostatic control compared to previous reports. This research sheds light on the potential of utilizing electrostatic doping scheme for low‐power electronics and opens a path toward novel designs of field programmable mixed analog/digital circuitry for reconfigurable computing. Abstract : By electrostatically tuning channel doping profiles, a triple‐gated 2D tungsten diselenide (WSe2 ) device can be operated as a diode, a tunneling or a metal‐oxide‐semiconductor field‐effect transistor (TFET/MOSFET). The best subthreshold swing among TFETs and the best ideality factor in diodes based on homogeneous 2D materials are reported. Self‐consistent simulations quantitatively agree with experiments and provide design guidelines for optimal performance.